Peran Kepuasan Nasabah Dalam Memediasi Pengaruh Kualitas Pelayanan Dan Literasi Produk Keuangan Terhadap Loyalitas Nasabah Bank Aceh Syariah - Kharisma, Siti Rahma Keumala; Nurdin, Ridwan (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
The purpose of this research is to examine the mediating influence of customer satisfaction on service quality and financial product literacy on customer loyalty at Bank Aceh Syariah. The sample in this study was 80 customers who were obtained using the Hair et al. formula. Data collection was carried out by distributing questionnaires to respondents which were then analyzed using structural model equations or SEM-PLS. This research found that service quality and product literacy have a positive and significant effect on customer satisfaction. Customer satisfaction and product literacy also have a positive and significant effect on customer loyalty. However, this result is inversely proportional to the influence of customer satisfaction on customer loyalty. Research also finds that service quality through customer satisfaction has a positive and significant influence on customer loyalty. However, in contrast to service quality, the financial product literacy variable found a positive but not significant influence on customer loyalty. To gain customer loyalty, Bank Aceh Syariah is advised to improve service quality. What can be done is to provide a polite and friendly welcome, make the waiting room comfortable and provide fast and efficient service.